REVOLUTIONARY CHANGES IN THE PHONETICS OF OLD ENGLISH FOR LINGUISTS - Boymurodova Feruza Ziyot qizi; Narzillayeva Sarvinoz Rustam qizi (Western European Studies, 2025)
This article focuses on the profound transformations that occurred in Old English phonetics over the periods. It explores key shifts, including great vowel shifts and grammatical endings, highlighting how these changes affected the perception of words. Furthermore, this paper will involve the introduction of new sounds on pronunciation. By comprehending these phonetic revolutions, linguists can achieve a more authentic and engaging point of Old English in their academic research papers as well as teaching. Old English is a crucial stage in the development of English language. Knowledge of Old English phonetics allows linguists to compare various language families together, particularly Roman-German languages. Over and above that, understanding the principal alterations can pave the way to read Old English texts and books authentically and for teaching the language accurately. This article will further enhance appreciation and bonds of literary works like “Beowulf” which is an Old English epic poem consisting of Germanic heroic legends. Finally, this article will end by illustrating some exact examples for the phonetic changes in the alphabet of English, based on professional research works by English linguists.
Keywords: the introduction of new sounds on pronunciation; great vowel shifts